Lost in Translation? Applying the Hate Crime Concept to an Indian Context - Bhat, M. Mohsin Alam (Journal of interpersonal violence, 2024)
Hate crime is increasingly a familiar term within the domains of scholarship, policy, and activism as the harms associated with acts of targeted hostility continue to pose complex, global challenges. However, an exclusively Western-centric focus has done little to foster transnational conversations or to shape conceptual or legal frameworks in parts of the world where the challenges posed by hate and prejudice remain underexplored despite their devastating consequences. This article considers how the complexities and specificities of the Indian context disrupt the dominant assumptions of conventional hate crime frameworks. In doing so, it highlights the value of extending conventional Westernized models of thinking to different environments with different sets of challenges. Through its analysis of caste crimes and the factors that reinforce a prevailing institutional and cultural backdrop of political indifference, bureaucratic resistance, and public skepticism, the article illustrates why and how key elements of the Western framework remain ill-suited to the Indian context. The authors call instead for a creative translation of the hate crime concept, which accommodates the nature of violence within specific social contexts, and which emphasizes the institutional features that can mitigate the limitations of state capacity and intent. The process of translation has value in harnessing the benefits of the hate crime concept within countries, which lack a common framework to foster shared understanding and prioritization in relation to tackling contemporary expressions of hate. At the same time, this process enriches prevailing thinking, dismantles stereotypes, and challenges scholars of targeted violence to familiarize themselves with the unfamiliar.